The Impact of Auditor Quality, Financial Stability, and Financial Target for Fraudulent Financial Statement - Arif Darmawan; Sariati Oktoria Saragih (Journal of Applied Accounting and Taxation, 2017)
This study analyzes the influence of financial stability, financial targets and the role of the quality of auditors against fraud measures financial statements. This study using purposive sampling and use of the 21 companies that commit fraud recorded in the financial statements of the Financial Services Authority and 21 companies did not commit fraud which includes compass 100 in the Indonesia Stock Exchange using logistic regression analysis. The study found a positive effect of variable quality auditor against fraudulent financial reports, found a negative influence financial stability and financial variables against the target of fraudulent financial statements. Limitation of this study are limited variables and proxy variables used to measure financial targets, further research is recommended to add the variables that affect the occurrence of acts of fraud financial statements, and look for a proxy for a target financial variables.